Folklore style in Azerbaijani children’s literature of the early 20th century - XURAMAN (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2025)
In the early 20th century, the enlightenment movement in Azerbaijan expanded significantly, providing a strong impetus for the emergence and development of children’s literature in the country. The educators and writers of that period made invaluable contributions to the process of national self-consciousness through their literary creativity. By drawing on various genres and themes from Azerbaijani folklore, they created some of the most notable examples of children’s literature. Enduring exemplars of national children’s poetry—rooted in oral folk traditions—began to emerge during this period. Traditional genres such as tapmaca (riddles), layla, sanama (counting-out rhyme), duzgu, yanıltmac (alliteration), and qaravalli were among the forms most frequently employed by children’s literature authors. Epics, folk tales, legends, and narratives provided the best thematic source material for their creative works. Each of these works continues to attract young readers today in terms of language and style, form and content, rhythm, as well as overall appeal. At that time, there were virtually no literary works available for classroom use in Azerbaijani schools that met pedagogical requirements and resonated with the interests and thought processes of children. The educators and writers of the period primarily composed the first children’s works for use in the educational process. These literary examples predominantly address moral and didactic themes, promote national and spiritual values, and contribute to the enrichment of one’s worldview. Mikayıl Müşfiq, Abdulla Şaiq, Abbas Səhhət, Mirzə Ələkbər Sabir, and others, are counted among the authors of the earliest children’s works written in the folklore style.